Low power and high voltage swing cascode Pierce oscillator for MEMS SAW resonators - Md Hamzah, Mohd Haidar; Nordin, Anis Nurashikin; Karim, Jamilah (IEEE, 2016)
The design of a cascode Pierce oscillator circuit with separation supply for a MEMS surface acoustic wave resonator is proposed. The cascode Pierce topology provides sufficient gain to counteract the high insertion losses of -65dB at 1.3GHz of the SAW resonator. This circuit was designed using Silterra's 0.13um CMOS process and has low power consumption of 1.52mW with high voltage swing 0.10V to 0.99V. All simulations were conducted using Cadence Design Systems. Simulated Phase Noise is 92.63dBc at 1MHz.